PUBLIC SECTOR AND ECONOMIC GROWTH; A PARADOLOGICAL ANALYSIS OF FISCAL FUNCTIONS AND SUSTAINABILITY IN NIGERIA (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
The  Nigerian  experience  with  public  sector  finance  management demonstrates fiscal  irresponsibility. In Nigeria,  the public  sector  is comprised of the Federal, State, and Local governments, as well as parastatals and organizations that provide public goods and services. Nigeria's public  sector,  with  its  diverse financing  sources, plays  a critical role in economic management via the creation and execution of economic  policies,   efficient   budgeting   and  planning   targeted   at attaining domestic and external balancing goals. The purpose of this research  was  to  determine  the  influence  of public  sector financial management on the sustainability of economic development in Nigeria. The research examined the influence on real gross domestic product of total federally collected income and total government spending.  The Autoregressive Distributive Lag (ARDL) technique was used to analyze data spanning the years 1986 to 2020. To begin, the findings indicate that there is no long-run association between public sector financial management and the sustainability of economic development in Nigeria. Second,   overall federal  revenue   was  shown   to   have   a positive association with real gross domestic product.  Thirdly, public sector financial management has no discernible influence on the sustainability of economic development in Nigeria. This report recommends that the ideal of sound public sector financial management be embraced in order to strengthen the sustainability of economic development in Nigeria via an  effective,  efficient,  and  transparent public  account  management system.